Estimating biological changes in human by different markers from RF exposure using modeling and measurements - Uluaydın, Niyazi Korkut. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
This thesis dissertation reviews the works of academia on natural occurring electrical, magnetic, and electromagnetic (EM) phenomena and their subtle relations with living organisms. It also investigates the artificial electromagnetic waves from different generations of mobile technology radio frequency (RF) exposure with their possible paths of impact. It proposes new scenarios of mobile technology usage through finite element method (FEM) simulations with new radio possibilities of mobile terminals and base stations in view of new antenna technologies. The model theoretical limitations are cross-checked by Mie Theory. The FEM simulations are first time oriented according to organ specific effect investigations in IEEE SAM phantom model. The simulations are also improved in terms of organ details such as eye-based ones with detailed initial conditions. This dissertation also first time projects the known EM effects on salivary glands by biological markers over hypothalamus-pituitary-adrenal (HPA) axis and pineal glands, which are similar in biological and electrical properties and cannot be studied without invasive methods. This is a solid non-thermal effect proposition on the homeostasis of human beings. This dissertation proposes a detailed measurement of the multi-operator multi technology urban base stations with spectrum and antenna aware methodology. Combining this with the statistics of mobile radio network maintenance activities with their periodicity and duration, which have never been reported before in academia, it provides a totally different perspective for occupational RF exposure and increased risks. Result of both probable non-thermal and thermal risks are clear findings new to the academia.
Keywords: Radio frequency.; Electromagnetic compatibility.